Os efeitos da orientação para serviço, na cocriação e na avaliação on-line no setor hoteleiro - Hexsel, Helen Tomaz (Universidade do Vale do Rio dos Sinos, 2018)
The aim of an organization is to satisfy the needs and desires of the customer. For this, the organization must have service orientation. Therefore, the organization needs a basic set of organizational policies, practices and procedures to be able to deliver service excellence. When the hospitality industry understands that their future survival and growth depends upon creating and offering unique and memorable experiences for their customers, and realized that co-creation can be adopted to try to respond to customer expectations, their ability to co-create and their willingness to co-create will be the key to put co-creation in practice. Faced with this scenario the on-line reviews can be used as a way to comprehend the personal thoughts, reactions and opinions of the clients about the services that the organization offers. With this, is possible to analyze if the client really perceived an excellence in the services provided. Then, this research aims to analyze the effects of hotel service orientation (i) in their ability to co-create, (ii) in their willingness to co-create and (iii) in on-line reviews, and (iv) analyze the effect of ability to co-create have on willingness to co-create. Therefore, an exploratory study was made with 6 hotels, an attempt to get a better knowledge of how the studied constructs fits on the hotel sector to assist on the scales validation. Afterwards, a survey was realized with 155 hotels in the State of Rio Grande do Sul in order to investigate the aspects presented previously. The statistic technique used was Structural Equation Model (MEE). The results have shown that service orientation influences ability to co-create, willingness to co-create and on-line reviews positively. The explained variance has reached important indexes since service orientation explained 88,8% of ability to co-create, 33,3% of willingness to co-create and 33,3% of on-line reviews that hotels received by clients. On the other hand, ability to co-create has not presented influence on willingness to co-create. Thus, hotels should search a major service orientation to reach high levels of co-creation and better on-line reviews.
Keywords: Orientação para serviços; Habilidade de cocriação; Comportamento de cocriação; Avaliações on-line; Setor hoteleiro; Service orientation; Ability to co-create; Willingness to co-create; On-line reviews; Hospitality industry; ACCNPQ::Ciências Sociais Aplicadas::Administração